2014
DOI: 10.1080/03602559.2014.909484
|View full text |Cite
|
Sign up to set email alerts
|

Flammability and Thermal Properties of Zeolite-Filled High-Impact Polystyrene Composites

Abstract: Effect of zeolite and organically modified montmorillonite (MMT) clay on flammability of high-impact polystyrene (HIPS) with ammonium polyphosphate (APP) flame retardant was investigated. Composites were prepared by melt blending in a twin-screw extruder, and it was found that zeolite and APP improve fire performance of HIPS with optimal concentration of 4 mass % of zeolite. Samples with MMT/APP and zeolite/APP have similar results of flammability, yet combination MMT/zeolite/APP had no additional improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…All fire retarded samples generally have lower average Ea values (in the region α = 0.2-0.9) than pure HIPS which could lead to conclusion that HIPS has higher thermal stability and slower degradation rate. Our previous studies [1,3,32] show that is not the case. Since Ea is only one part of kinetic triplet, it is possible that difference in frequency factor, A, of composites compensates their lower Ea when compared to HIPS.…”
Section: Isoconversional Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…All fire retarded samples generally have lower average Ea values (in the region α = 0.2-0.9) than pure HIPS which could lead to conclusion that HIPS has higher thermal stability and slower degradation rate. Our previous studies [1,3,32] show that is not the case. Since Ea is only one part of kinetic triplet, it is possible that difference in frequency factor, A, of composites compensates their lower Ea when compared to HIPS.…”
Section: Isoconversional Methodsmentioning
confidence: 85%
“…Lower values of Ea of fire retarded composites were overcompensated by the difference in A by a magnitude of four to five compared to HIPS thus giving overall slower degradation rate and higher thermal stability which is in accordance with previous research. [1,3,32] It seems from Figure 5 that sample PS-20AP-4C starts to degrade earlier than pure HIPS, but it has to be taken into account that it has weight residue at 500 °C of 20 % a) b)…”
Section: One Step Modellingmentioning
confidence: 99%
“…33,34 In order to improve the effect of the above flame retardants in HIPS, various synergists such as inorganic nanoparticles were often used. [26][27][28]32,35 AZONOR also displays a certain synergism in HIPS. 15 It has been reported that there is good synergism between magnesium hydroxide and microencapsulated red phosphorus in HIPS.…”
Section: Introductionmentioning
confidence: 98%
“…However, HIPS are flammable, thus underlining the importance of flame retardant treatments. The flame retardants used in HIPS are mainly phosphorus flame retardants, [23][24][25][26][27][28][29][30] metal hydroxides 23,24,31,32 and various brominated flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…So, the study to enhance its thermal stability and flame retardancy properties is required and highly demanded. Usually to improve the thermal stability and flame resistance of thermoplastic polymers flame retardant materials have to be used as additives [2,3]. Halogen-based flame retardants were used and these materials were found to be effective for flame retardation; however these materials were inhibited due to their associated environmental pollution [4][5][6].…”
Section: Introductionmentioning
confidence: 99%